Parent engagement in perinatal mortality reviews: an online survey of clinicians from six high‐income countries. (19th October 2020) - Boyle, FM; Horey, D; Siassakos, D; Burden, C; Bakhbakhi, D; Silver, RM; Flenady, V
Abstract : Objective: Parent engagement in perinatal mortality review meetings following stillbirth may benefit parents and improve patient safety. We investigated perinatal mortality review meeting practices, including the extent of parent engagement, based on self‐reports from healthcare professionals from maternity care facilities in six high‐income countries. Design: Cross‐sectional online survey. Setting: Australia, Canada, Ireland, New Zealand, UK and USA. Population: A total of 1104 healthcare professionals, comprising mainly obstetricians, gynaecologists, midwives and nurses. Methods: Data were drawn from responses to a survey covering stillbirth‐related topics. Open‐ and closed‐items that focused on 'Data quality on causes of stillbirth' were analysed. Main outcome measures: Healthcare professionals' self‐reported practices around perinatal mortality review meetings following stillbirth. Results: Most clinicians (81.0%) were aware of regular audit meetings to review stillbirth at their maternity facility, although this was true for only 35.5% of US respondents. For the 854 respondents whose facility held regular meetings, less than a third (31.1%) reported some form of parent engagement, and this was usually in the form of one‐way post‐meeting feedback. Across all six countries, only 17.1% of respondents described an explicit approach where parents provided input, received feedback and were represented at meetings. Conclusions: We found no established practice of involving parents in the perinatal mortality review process in six high‐income countries. Parent engagement may hold the key to important lessons for stillbirth prevention and care. Further understanding of approaches, barriers and enablers is warranted. Tweetable abstract: Parent engagement in mortality review after stillbirth is rare, based on data from six countries. We need to understand the barriers. Tweetable abstract: Parent engagement in mortality review after stillbirth is rare, based on data from six countries. We need to understand the barriers.